Pengaruh Layanan Penguasaan Konten Terhadap Peningkatan Kecerdasan Moral Siswa Kelas X SMA Negeri 10 Pekanbaru Tahun Ajaran 2013/2014 - Rahayu, Yoan Kusuma; Rosmawati, Rosmawati; Umari, Tri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract : This study aims to determine the effect of content mastery services to the increasing moral intelligence tenth grade student’s of SMA Negeri 10 Pekanbaru Academic Year 2013/2014. The method used in this study is the method of quasi experiment, using one group pretest - posttest design. And sampling in this study 25% of the total population using a random sampling technique, mastery of content services are used as a way to improve student’s moral intelligence through several treatments. The hypothesis of this study is that there is a difference of moral intelligence of student’s before and after the service carried on the content mastery 5% error level. From the results of the processing are used by researchers, the test results obtained by the correlation of the two variables mastery of content services contribute to the improvement of the moral intelligence of student’s by 37%. And then based on that of tgreater than ttable (- 16.89> 1.960). Based on the above it can be concluded that the mastery of content services well prepared as a highly effective intervention techniques to improve the moral intelligence of student’s in the school. Furthermore, researchers recommend to the supervising teacher or school counselor in order to carry out activities mastery of content services to students of class XI and XII in order to improve student’smoral intelligence or other positive behaviors. Keywords: Moral Intelligence, Content Mastery Services.WISUDA OKTOBER